Dysfunctional mitochondria in age-related neurodegeneration: Utility of melatonin as an antioxidant treatment - Reiter, Russel J. (2024)
As humans live longer, our bodies struggle to keep up. Organs like hips and hearts wear out, and our nervous system suffers as irreplaceable neurons die. This decline is linked to high energy use, which creates damaging molecules that accumulate over time. This free radical damage weakens neurons, contributing to age-related diseases and death. While these harmful molecules come from various sources, the energy-producing mitochondria are a major culprit. The more energy a cell uses, the faster it seems to age.To highlight, the pineal gland produces melatonin, a hormone that regulates sleep-wake cycles. Melatonin production declines with age, disrupting circadian rhythms and potentially contributing to age-related diseases. However, melatonin is also produced by other cells throughout the body, including brain cells. These cells use mitochondria, the energy centers of cells, to make melatonin. This local production may help protect brain cells from damage caused by free radicals, harmful molecules linked to aging. Studies suggest that melatonin production in the brain and other tissues can be stimulated in response to inflammation or other stressors. This may be a natural defense mechanism to combat free radical damage. Further research is needed to understand how melatonin production in different parts of the body works together to influence health and aging.